THE STUDENTS’ABILITY IN IDENTIFYING INDEPENDENTAND DEPENDENT CLAUSE IN SENTENCE AT TENTH GRADE OF PONDOK PESANTREN DARUL ARQOM PEMANTANG BANDAR - LUBIS, NURAINUN (Faculty of Tarbiyah nad Teacher Training, 2022)
This research is aims to determine the ability of students in identifying independent and dependent clauses in sentences in the Darul Arqom Persantren, Tenth grade students of SMK Darul Arqom. The population of this study was students of class X SMK-1 Darul Arqom, and by using total sampling, as many as 30 students were sampled in this study. To get the data, the writer prepared a test made by the teacher. This test is about identifying independent and dependent clauses. After obtaining the data, the researcher analyzed the percentage of students' abilities and calculated the proficiency index using the formula recommended by Arikunto. The results showed that 87% or about 26 students were considered